Emotion is the driving force of learning. (Journal of Parents and Teachers, 2025)
The article is based on the idea that for students and teachers to learn, they must be emotionally engaged with the subjects they are going to work on; that is, the content should not be presented as isolated facts but should establish synergies with the reality each child lives in. Additionally, 25 items are proposed to consider when working in this way in the classrooms